Destituting the Interface: Beyond Affordance and Determination - Torsten Andreasen (Media Theory)
This article proposes the affordance of the medium and the determination of the dispositif as two distinct approaches to media or technology in general. Taking the dialectical tension between affordance and determination, between medium and dispositif, as its point of departure, the article explores Transmute Collective’s Intimate Transactions (2005) as a problematic fusion of the two approaches. A historicising re-reading of Guy Debord’s Society of the Spectacle with regard to current forms of digital control and modes of production then argues that contemporary alienation takes place within the digital interface as the zone of indistinction between affordance and determination, and that instead of designing liberating machines or inventing subjective evasions of the dispositif, emancipatory engagement requires a destitution of the interface.